Analisis Maintenance Produktifitas pada Mesin Steel VMI untuk Menghitung Overall Equipment Effectiveness - Danang Aditya Pradana; sukanta sukanta; Rizki Ahmad Darajatun (Performa: Media Ilmiah Teknik Industri, 2020)
Companies engaged in the production of vehicle tires. In the production process, an assessment of the effectiveness of the machine is carried out, especially on the Steel VMI machine, which is carried out by the Industrial Engineering Department. The purpose of this research is to identify the cause of the problem with the low overall Equipment Effectiveness (OEE) value on the Steel VMI machine. In measuring the OEE value on the Steel VMI machine, suggestions are made to increase the low OEE value. Research methods for solving problems by calculating and analyzing the value of availability, value of performance and quality value and determination of six big losses. The results show that the availability value is 84%, the performance value is 71%, the quality value is 100%. Then, the cause of the low OEE value is the Human Error variable. Thus, the results of the measurement of the low OEE value are influenced by the performance value of 71%, while the largest six big loss value in the Equipment Failure losses variable is 1.88%, then the Chokotei / Idling Minor Stoppage variable is 9.1%